2014
DOI: 10.5935/0034-7167.20140042
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual reflections on health humanization: conception of nurses from Intensive Care Units

Abstract: se configura como uma política pública complexa que abarca os aspectos estruturais, técnicos e relacionais do serviço de saúde, não estabelecendo as demarcações de suas atividades e com isso também uma deficiência em termos conceituais da humanização. Este estudo teve por objetivo realizar uma reflexão acerca da humanização da saúde, através de uma análise conceitual do próprio termo na interpretação das falas de enfermeiros assistencialistas atuantes em Unidades de Terapia Intensiva, coletadas numa pesquisa q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
1
5
0
5
Order By: Relevance
“…Still about the practice of humanized care, the literature review for this research points out that empathy, singularity, and integrality have been the most representative expressions of the way professionals of the multidisciplinary team conceive the practice of humanized care, and our results corroborate this foundation (12,17,(21)(22)(23)(24) .…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Still about the practice of humanized care, the literature review for this research points out that empathy, singularity, and integrality have been the most representative expressions of the way professionals of the multidisciplinary team conceive the practice of humanized care, and our results corroborate this foundation (12,17,(21)(22)(23)(24) .…”
Section: Discussionsupporting
confidence: 79%
“…The humanization of ICU care was researched by Mongiovi, Anjos, Soares, e Lago-Falcão (22) and it meets the results of this research when discussing the importance of the empathy, also as a constituent factor and concept. Other researches that involve health-care workers and users allow the identification of the connection between humanization of the care and empathy, representing an essential tool for the operationalization of this practice (11,(17)(18)23) .…”
Section: Discussionmentioning
confidence: 99%
“…Exames intrabucais avaliaram as condições orais mostrando uma história de perda de dentes, a qual teve a média de 17,62 dentes em boca por indivíduo, com um total de 1022 dentes avaliados (Quadro-1). O estudo deixa claro que o Enfermeiro é capaz de executar a simples atividade de diagnóstico da gengivite, principalmente, por se tratar de um exame simples, não doloroso e não invasivo; outro ponto que fortalece a hipótese do enfermeiro poder realizar o exame é que suas atividades no hospital relacionamse com responsabilidades relevantes e complexas como o trabalho em ambiente de terapia intensiva, troca de curativos e realização de partos, além da visão holística contrapondo o modelo biomédico 13 . Importante destacar que não é objetivo do estudo criar novas responsabilidades, mas propor parcerias de áreas de conhecimento afins com a odontologia.…”
Section: Resultsunclassified
“…He verified that from the perspective of the relatives, It is verified that the lived experience of the family reveals peculiarities of enormous suffering. It is known, according to some authors, that when continued and intense, it can result in important emotional, psychosocial and structural changes in the individual and family domain (8,(18)(19) . It has been found that two key determinants contributed to this experience, namely the fact that it is unpredictable and associated with the idea of threating the life of the person now hospitalized.…”
Section: Discussionmentioning
confidence: 99%